Addressing Indonesia's Infrastructure Deficit. Issue 1 (2nd January 2016) - Ray, David; Ing, Lili Yan
Abstract : Between September 2015 and February 2016, the government of President Joko Widodo (Jokowi) unveiled 10 economic policy packages in an effort to promote deregulation and support investment in key sectors. Foreign investors, at whom many of these measures are directed, have viewed the packages with a mix of cautious optimism and healthy scepticism. Investors have often heard Jokowi announce that Indonesia welcomes foreign capital, only to see these commitments countermanded by the actions of ministers and officials wanting more restrictive regulations and practices. It therefore remains uncertain whether these announcements and policy packages will lead to actual reform. One area in which the government is showing both intent and progress is infrastructure. Decades of under-investment and poor asset management have left Indonesia with a major infrastructure deficit, the economic and social costs of which are substantial. There are encouraging signs, however. Jokowi's administration is continuing its agenda of fiscal reform, shifting budget allocations away from energy subsidies and towards capital spending; investment approvals in infrastructure are rising fast; and the country's four largest construction firms have reported a large jump in the value of government-awarded contracts. Recent months have also seen the completion of the Makassar–Parepare segment of the Trans-Sulawesi railway and the first stage of the New Priok Port at Tanjung Priok, while the long-awaited Umbulan Springs project, which will supply water to Surabaya and surrounding areas, has been awarded to a preferred bidder. Demonstrating rapid progress in delivering infrastructure is clearly important to the Jokowi administration, but longer-term challenges remain. For one, Indonesia's inefficient planning and delivery model for national roads needs to be overhauled if the country is to safeguard its economic growth. The government has yet to fully tackle this and other long-term reforms; it has, however, recently introduced regulations that augur well for new flows of private investment, such as reinstating the role of such investment in the water sector and allowing for a more realistic risk allocation in public–private partnerships.